Design, application and evaluation of strategies that contribute to the construction and dissemination of a quality culture in Medical Education in a Mexican medical school - Rodríguez Garza, Mayela del Refugio; Ruiz Flores, Pablo (Avances en Supervisión Educativa, 2010)
The research oriented to design, apply and evaluate educational intervention strategies to make aware to teachers and students from Coahuila’s Autonomy University Medical Faculty, about the importance of building and spreading a quality culture into medical education, helping through education member’s information and training to develop attitudes for a quality culture. It was needed a point to start from the reality that lives the Faculty, being more precise in the design of intervention strategies helping a change of attitude to the Faculty’s educative quality, it was started with a strategy diagnostic which results determined the quality indicators that would help this investigation. The teacher’s attitude dimension indicators were: teacher’s training & actualization, teacher’s boarding work, lesson planning and evaluation. The ones for the had 2 measurement periods: one before intervention strategies application (school year 2003-2004) and another one after the intervention strategies application (school year 2004-2005). The program consisted in diffusion activities: posters and flyers, 4 conferences for the students and 4 conferences for the teachers, a teacher’s training actualization course-workshop, and implementing 2 proposals: one Educative Managing, the other one about Forming Values, which base was done at the teacher’s boarding work. The research was done with 350 students and 68 teachers. The tools designed to measure attitude were 2: one for the students with 18 questions and another one for the teachers containing 12 questions. About the results gotten, it can be said that change was more notorious in students, in which an indicator got the maximum point (team work) while the other ones rose about more than 100% (taking decisions and critical judgment). About the teachers, some changes werw observed in the 4 indicators, 2 of them showed a low rising (teacher’s training, actualization and evaluation) Finally in the teacher’s evaluation done by the students it’s evident that teacher’s job performance did not get better, for example, following the program and attendance was barely high. That indicates students were more aware than teachers about changing attitude and had better performing results as a cosequence of applying strategies.